2019
DOI: 10.3390/nu11030539
|View full text |Cite
|
Sign up to set email alerts
|

Understanding How Consumers Categorise Health Related Claims on Foods: A Consumer-Derived Typology of Health-Related Claims

Abstract: The Nutrition and Health Claims Regulation (NHCR) EC No 1924/2006 aims to provide an appropriate level of consumer protection whilst supporting future innovation and fair competition within the EU food industry. However, consumers’ interpretation of health claims is less well understood. There is a lack of evidence on the extent to which consumers are able to understand claims defined by this regulatory framework. Utilising the Multiple Sort Procedure (MSP), a study was performed (N = 100 participants across f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…Some factors related to customers may also be important to the effect of NCs. Nutrition knowledge, motivation to adopt a healthy diet, health consciousness and consumers’ difficulty to understand claims may modulate the effect of NCs [ 9 , 10 , 13 , 14 , 15 , 16 ]. As a summary of all the potential factors influencing the effect of NCs on food choices, Oostenbach proposed a conceptual model in 2019 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some factors related to customers may also be important to the effect of NCs. Nutrition knowledge, motivation to adopt a healthy diet, health consciousness and consumers’ difficulty to understand claims may modulate the effect of NCs [ 9 , 10 , 13 , 14 , 15 , 16 ]. As a summary of all the potential factors influencing the effect of NCs on food choices, Oostenbach proposed a conceptual model in 2019 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The definition of the term ‘healthy’ is not always consistent, and nuances and subjective conceptualizations persist among consumers [ 1 ]. Scholars and researchers have paid significant attention to health claims, and particular emphasis has been placed on labels reporting the nutrition and healthiness of foods [ 4 , 5 , 6 ], that aim to allow consumers to also better identify functional foods, even in the absence of direct or specific knowledge. Recent studies on consumers’ perceptions of the healthiness of olive oil have indicated that consumers feel that it is a naturally healthy food.…”
Section: Introductionmentioning
confidence: 99%
“…2017; Hodgkins et al . 2019; Hung & Verbeke 2019) and this article aims to outline the background and rationale for an EIT Food‐funded project in this area, with the consumer‐facing title Health Claims Unpacked .…”
Section: Introductionmentioning
confidence: 99%